PERAN PENGGUNAAN MEDIA ONLINE DALAM PENERIMAAN MAHASISWA BARU - Nina Dewi Lashwaty; Ina Sholihah Widiati; Hadis Turmudi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
Technological advances especially in the field of information increase the speed of change in all areas of life, including in a company's marketing strategy. STMIK Amikom Surakarta is an educational service provider that has made changes in its marketing methods. Marketing to attract prospective new students is not only done in conventional ways but also includes the use of information technology applications in the form of online media such as websites (web ), whatsapp (WA), instagram (IG), and facebook (Fb). This research was conducted with the aim to find out the use of online media in marketing and its effect on admission of new students at STMIK Amikom Surakarta Academic Year 2019/2020. The type of research is a quantitative econometric approach. Hypothesis testing uses Multiple Linear Regression Analysis, F Test, t Test, and Determination Coefficient Analysis (R2). Reliability test using Cronbach Alpha. Based on the Regression Coefficient it is known that the use of website, whatsapp, and instagram has a positive influence on the admission of new students, while the use of facebook is negative which means it has an opposite relationship. From the F Test result it is known that the simultaneous use of website, whatsapp, instagram, and facebook significantly influences the admission of new students. The t test stated that partially the use of website and whatsapp had a positive and significant effect on admission of new students. While the partial use of instagram has no contribution, even the partial use of facebook besides having no contribution also has an opposite relationship with the admission of new students